Revealing The Women’s Characteristics Presented In L’oreal Paris Shampoo Advertisements: A Semiotic Study - Nathaniela Anita Kiroyan; Yulius Kurniawan; Endar Rachmawaty Linuwih (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2023)
Nathaniela Anita Kiroyan(2023). Visual and Verbal Signs Found in L’oreal Paris Shampoo Advertisements. S1. Thesis. English Department. Widya Kartika University. Surabaya. Advisor I: Yulius Kurniawan, S.Pd., M.Pd.; Advisor II: Endar Rachmawaty Linuwih, S.Hum., M.Pd. The purpose of this research is to find out the visual and verbal signs in L’Oréal Paris shampoo advertisements and to explain the visual and verbal signs and meaning that are represented in L’Oréal Paris shampoo advertisements by using semiotics theory by Roland Barthes. This research used a descriptive qualitative method to analyze the collected signs in the whole picture of the advertisement of L’Oréal Paris shampoo. In addition, the researcher collected the data from Pearl Chemist Group which had the best of five of L’Oréal Paris shampoo advertisements. The findings indicate denotative meanings of signs revealed were black hair, long hair, wavy hair, woman, smiling face, purple dress, purple shirt, orange background, black belt, and products of L’Oréal Paris shampoo. The connotative meanings of the signs revealed elegance, friendliness, confidence and self-esteem, freedom of expression and creativity, and empowerment of women.